2018
DOI: 10.1016/j.molp.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Oximes: Unrecognized Chameleons in General and Specialized Plant Metabolism

Abstract: Oximes (RRC=NOH) are nitrogen-containing chemical constituents that are formed in species representing all kingdoms of life. In plants, oximes are positioned at important metabolic bifurcation points between general and specialized metabolism. The majority of plant oximes are amino acid-derived metabolites formed by the action of a cytochrome P450 from the CYP79 family. Auxin, cyanogenic glucosides, glucosinolates, and a number of other bioactive specialized metabolites including volatiles are produced from ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 181 publications
2
117
0
Order By: Relevance
“…It appears that the accumulation of aldoximes or their derivatives limits phenylpropanoid production (Hemm et al, 2003;Kim et al, 2015). Because aldoximes are precursors of many other biomolecules besides glucosinolates, including cyanogenic glucosides and nitriles, and can be found in diverse plant species such as maize, poplar, yew and coca (Irmisch et al, 2013(Irmisch et al, , 2015Luck et al, 2017;Sørensen et al, 2018;Bhalla et al, 2018;Dhandapani et al, 2019), aldoxime-mediated suppression of phenylpropanoid metabolism may be relevant to other species and metabolic pathways beyond Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the accumulation of aldoximes or their derivatives limits phenylpropanoid production (Hemm et al, 2003;Kim et al, 2015). Because aldoximes are precursors of many other biomolecules besides glucosinolates, including cyanogenic glucosides and nitriles, and can be found in diverse plant species such as maize, poplar, yew and coca (Irmisch et al, 2013(Irmisch et al, , 2015Luck et al, 2017;Sørensen et al, 2018;Bhalla et al, 2018;Dhandapani et al, 2019), aldoxime-mediated suppression of phenylpropanoid metabolism may be relevant to other species and metabolic pathways beyond Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…281 Heteroatom oxidation by P450 enzymes has been widely reported, 12 and although such reactions are oen found in xenobiotic metabolism, NocL serves as an important reminder that the role of P450s in heteroatom oxidation during secondary metabolism cannot be discounted.…”
mentioning
confidence: 99%
“…Because aldoximes are precursors of many other biomolecules besides glucosinolates, including cyanogenic glucosides and nitriles, and can be found in diverse plant species such as maize, poplar, yew and coca (Irmisch et al, 2013(Irmisch et al, , 2015Luck et al, 2017;Bhalla et al, 2018;Sørensen et al, 2018;Dhandapani et al, 2019), aldoxime-mediated suppression of phenylpropanoid metabolism may be relevant to other species and metabolic pathways beyond Arabidopsis. Previous work showed that glucosinolate/phenylpropanoid crosstalk requires MED5 (Kim et al, 2015), but its underlying mechanism was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our transcriptome analyses and genetic study with a set of glucosinolate-deficient mutants reveal that the accumulation of aldoximes or their derivatives affects expression of a specific group of F-box genes, thereby altering the stability of PAL, as well as acting to negatively affect at least one other step of phenylpropanoid metabolism. Considering that aldoximes are precursors of important biomolecules and that the oxime-producing CYP79s are widespread in higher plants (Sørensen et al, 2018), this crosstalk may be relevant not only to glucosinolates but also to other metabolic pathways.…”
Section: Researchmentioning
confidence: 99%